The evolution of inequality in Mozambique: 1996/97-2019/20 - Giulia Barletta; Maimuna Ibraimo; Vincenzo Salvucci; Enilde Sarmento; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
After decades of war, ending in 1992, Mozambique embarked on a path of sustained economic growth and substantial poverty reduction. However, these positive dynamics started to revert from 2015, with per capita growth rates getting close to zero and household real consumption reducing in all areas of the country. Meanwhile, inequality stagnated in the period 1996/97-2008/09, before markedly increasing afterwards. In this study, we analyse some of the most relevant indicators of inequality for Mozambique and their trends over the last 25 years. Using real per capita consumption as the main welfare aggregate, we look at various indicators of inequality, including the consumption distribution, percentiles and percentile ratios, growth incidence curves, Lorenz curves, and Gini indices at the national and subnational levels. In addition, we discuss spatial inequality between urban and rural areas and between regions. Overall, we find that until 2014/15 consumption increased for the whole population, but it did so much more for richer households, leaving the worse-off behind; conversely, in the last few years consumption has reduced across the distribution, but the relative consumption gap between better- and the worse-off people has continued to increase.
Keywords: D31; D63; O15; 330; inequality; consumption distribution; spatial inequality; Mozambique